Origins of the discipline of Human Resources Management in a Faculty of Economics and Business - Acuña A., Eduardo; Muga M., José Antonio; Trincado M., Francisco; Pedreros M., Pedro (Estudios de Administración, 2014)
This paper describes and analyses the evolution of the Human Resources Management Discipline in its evolution, genesis process, development, change and institunalization at the currentBusiness Management School (FEN) at the Universidad de Chile from a historical and heuristic perspective from the 1958- 1973 period.